Castleman's Disease and Neutropenic Enterocolitis Presenting as Crohn’s Disease - Kelly W Burak; Ronald J Bridges; Walter B Blahey (Canadian Journal of Gastroenterology)
A rare case of Castleman's disease presenting as Crohn's disease is described. This 21-year-old male with chronic neutropenia for one year presented with recurrent right lower quadrant pain of two years' duration. Small bowel follow-through suggested Crohn's of the terminal ileum. Colonoscopy confirmed ulcerations in the terminal ileum and cecum, with biopsies showing necrosis and inflammation. Treatment was initiated with prednisone, 5-aminosalicylate and granulocyte colony-stimulating factor for neutropenia. Symptoms recurred one year later, and repeat colonoscopy showed a focal cecal ulceration. Two years after presentation a resection was planned. Laparotomy revealed a normal ileocecal region and a large retroperitoneal mass of lymphadenopathy. Biopsies confirmed reactive hyperplasia, consistent with the plasma cell variant of Castleman's disease. Chemotherapy has resulted in improvement of symptoms and decrease in mass size, but cecal ulceration persisted. This case illustrates a variant presentation of Castleman's disease with neutropenia and manifestations in the gastrointestinal tract.